Children's speech an evidence-based approach to assessment and intervention - McLeod, Sharynne; Baker, Elise (Pearson, 2017)
"This book distills scientific evidence from around the world on sound disorders across the areas of speech acquisition, assessment, analysis, diagnosis, and intervention, and presents it with practical knowledge to prepare speech-language pathologists (SLPs) to work with children and their families. The book is guided by two contemporary frameworks that direct the successful management of speech sound disorders in children: evidence-based practice (EBP) and the International Classification of Functioning Disability and Health--Children and Youth (ICF-CY)."--Publisher.